Jean Rhys Twenty-First-Century Approaches - Johnson, Erica (Edinburgh University Press, 2022)
Presents new critical perspectives on Jean Rhys in relation to modernism, postcolonialism, and theories of affectJean Rhys (1890-1979) is the author of five novels and over seventy short stories. She has played a major figure in debates attempting to establish the parameters of postcolonial and particularly Caribbean studies, and although she has long been seen as a modernist writer, she has also been marginalized as one who is not quite in, yet not quite out, either. The 10 newly commissioned essays and introduction collected in this volume demonstrate Jean Rhys's centrality to modernism and to postcolonial literature alike by addressing her stories and novels from the 1920s and 1930s, including Voyage in the Dark, Quartet, After Leaving Mr. Mackenzie, and Good Morning, Midnight, as well as her later bestseller, Wide Sargasso Sea (1966). The volume establishes Rhys as a major author with relevance to a number of different critical discourses, and includes a path-breaking section on affect theory that shows how contemporary interest in Rhys correlates with the recent 'affective turn' in the social sciences and humanities. As this collection shows, strangely haunting and deeply unsettling, Rhys's portraits of dispossessed women living in the early and late twentieth-century continue to trouble easy conceptualisations and critical categories.Key Features:New and original work on Jean Rhys's fiction and short stories, highlighting key areas of her work.Contributors are leading scholars on Jean Rhys from the US, the UK, and Australia, including Mary Lou Emery, Elaine Savory, John J. Su, Maroula Joannou, H. Adlai Murdoch, Rishona Zimring, Carine Mardorossian, Patricia Moran, Erica L. Johnson, and Sue Thomas.Organised around 3 important themes: Rhys and modernism, postcolonial Rhys, and affective Rhys